Profile of Colorectal Cancer at Sanjiwani General Hospital, Gianyar Period January 2020 – June 2022 - Ni Kadek Seri Mahayanti; I Wayan Eka Saputra (HM Publisher, 2022)
Background: Colorectal cancer is one of the most common cancers worldwide and the third leading cause of cancer death in the UK and the United States. There were 1.8 million new colorectal cancer cases and 881,000 deaths. This study aims to determine the profile of colorectal cancer at Sanjiwani General Hospital for the period January 2020 - June 2022. Methods: This study is a descriptive study using secondary data from archives at the Anatomical Pathology Installation of the Sanjiwani General Hospital for the period January 2020 – June 2022. Data collection in the form of gender, age, cancer location, and histopathological type was carried out using the convenient purposive sampling method. Results: This study showed that the highest age group was the age group 61-70 years 32.6%, the sex was mostly male 63.9% with the most common location of colorectal cancer found in the rectum 66.2% and the histopathological type in the form of adenocarcinoma 96.5%. Conclusion: Most of the cases were found in the male gender, and the age range was 61-70 years. Most cancer locations were found in the rectum with the histopathological type of adenocarcinoma.